Drivers of inorganic carbon dynamics in first‐year sea ice: A model study. Issue 1 (29th January 2015) - Moreau, Sébastien; Vancoppenolle, Martin; Delille, Bruno; Tison, Jean‐Louis; Zhou, Jiayun; Kotovitch, Marie; Thomas, David N.; Geilfus, Nicolas‐Xavier; Goosse, Hugues
Abstract Sea ice is an active source or a sink for carbon dioxide (CO2), although to what extent is not clear. Here, we analyze CO2 dynamics within sea ice using a one‐dimensional halothermodynamic sea ice model including gas physics and carbon biogeochemistry. The ice‐ocean fluxes, and vertical transport, of total dissolved inorganic carbon (DIC) and total alkalinity (TA) are represented using fluid transport equations. Carbonate chemistry, the consumption, and release of CO2 by primary production and respiration, the precipitation and dissolution of ikaite (CaCO3·6H2O) and ice‐air CO2 fluxes, are also included. The model is evaluated using observations from a 6 month field study at Point Barrow, Alaska, and an ice‐tank experiment. At Barrow, results show that the DIC budget is mainly driven by physical processes, wheras brine‐air CO2 fluxes, ikaite formation, and net primary production, are secondary factors. In terms of ice‐atmosphere CO2 exchanges, sea ice is a net CO2 source and sink in winter and summer, respectively. The formulation of the ice‐atmosphere CO2 flux impacts the simulated near‐surface CO2 partial pressure (pCO2), but not the DIC budget. Because the simulated ice‐atmosphere CO2 fluxes are limited by DIC stocks, and therefore <2 mmol m−2 d−1, we argue that the observed much larger CO2 fluxes from eddy covariance retrievals cannot be explained by a sea ice direct source and must involve other processes or other sources of CO2. Finally, the simulations suggest that near‐surface TA/DIC ratios of ∼2, sometimes used as an indicator of calcification, would rather suggest outgassing.